A comparison of the parasitoid wasp species richness of tropical forest sites in Peru and Uganda – subfamily Rhyssinae (Hymenoptera: Ichneumonidae) - Hopkins, Tapani; Tuomisto, Hanna; Gómez, Isrrael C.; Sääksjärvi, Ilari E. (Peer Community Journal)

(untitled)
The global distribution of parasitoid wasp species richness is poorly known. Past attempts to compare data from different sites have been hampered by small sample sizes and lack of standardisation. During the past decades, we have carried out long-term Malaise trapping using a standardised approach in the tropical forests of Peru (western Amazonia) and Uganda (eastern Africa). Here, we test how well such data can be used for global comparisons, by comparing the results for the subfamily Rhyssinae (Hymenoptera: Ichneumonidae). We found that more rhyssine species were caught in Peru than in Uganda, despite the Ugandan samples containing many more individuals both in absolute terms and per unit time. The difference in the number of individuals caught may largely be due to more rainfall in Peru, since rain reduces Malaise trap catches. Peruvian traps caught species at a faster rate (per individual caught) than Ugandan traps. We interpret this as a sign that the Peruvian sites have more species than the Ugandan site. Long-term, standardised Malaise trapping showed promise for global comparisons of species richness. Sampling more sites on both continents, and analysing all subfamilies, would give an estimate of which continent has more parasitoid wasp species. We suggest some refinements to the sampling design that would further improve sampling efficiency for future studies.